Prevalence of Mid-Mesial Canal and Isthmuses in Mandibular First and Second Molars in an Iranian Population - F Shakeri; H Azizi; F Razian; S Haghanifar; N Hoshyari (Islamic Azad University, 2019)
Background and Aim: It is essential to know the internal root canal anatomy to reach a successful root canal debridement and a subsequent successful root canal obturation. Due to the importance of knowing the complexity of mid-mesial (MM) canals and isthmuses and how to deal with these anatomic variations, in this study, we examined the incidence and prevalence of the MM canal and isthmuses in mandibular first and second molars. Materials and Methods: In this cross-sectional study, cone-beam computed tomography (CBCT) records of patients presenting for diagnostic purposes to a radiology center in the city of Sari were used. A total of 207 mandibular first molars (81 males and 126 females) and 235 mandibular second molars (94 males and 140 females) were examined. Data were entered into SPSS 16 software. Descriptive data were presented using frequency percentage with the significance level of less than 0.05. Results: Among the mandibular first molars that were examined in the study population, the prevalence of the MM canal was reported to be 2.5% in males and 4% in females. Similarly, the prevalence of the MM canal in the mandibular second molars was reported to be 2.1% in males and 3.6% in females. Also, the prevalence of isthmuses was 81.2% (males) and 78.9% (females) in the first molars and 78.7% (males) and 70.7% (females) in the second molars. Conclusion: Based on the results of this study, it is important for dentists to be familiar with the root canal anatomy and to consider the referral of complex cases to endodontists.